2018
DOI: 10.1134/s0022476618070120
|View full text |Cite
|
Sign up to set email alerts
|

Hirshfeld Surface Analysis, Crystal Structure and Spectroscopic Studies of a New Cu(II) Halocuprate Salt with Protonated N-Amino-Ethyl-Piperazine

Abstract: (C6H18N3)4[CuCl5]2[CuCl4]3ꞏ1.42H2O has been prepared and characterized by various physicochemical techniques. Single crystal X-ray diffraction structural analysis has revealed that the title compound belongs to the orthorhombic system with space group Cmca. Its unit cell dimensions are: a = 24.286 (2) Å, b = 14.3082 (14) Å, c = 16.6160 (16) Å, with Z = 4, V = 5773.8 (10) Å 3 and its crystal structure was determined and refined down to R= 0.024 and wR (F 2) = 0.059. The structure contains three crystallographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This distortion is too large to be attributed uniquely to the structural disorder involving the Cl1 site and suggests the involvement of the Cl atoms in a complex system of N-HÁ Á ÁCl hydrogen bonds as being responsible of the phenomenon. In the organic entity, the morpholine ring adopts a typical chair confirmation and all the geometrical features agree with those found in 4-(2-ammonioethyl)morpholin-4-ium tetrachloridozincate (El Glaoui et al, 2008;Lamshö ft et al, 2011).…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…This distortion is too large to be attributed uniquely to the structural disorder involving the Cl1 site and suggests the involvement of the Cl atoms in a complex system of N-HÁ Á ÁCl hydrogen bonds as being responsible of the phenomenon. In the organic entity, the morpholine ring adopts a typical chair confirmation and all the geometrical features agree with those found in 4-(2-ammonioethyl)morpholin-4-ium tetrachloridozincate (El Glaoui et al, 2008;Lamshö ft et al, 2011).…”
Section: Figuresupporting
confidence: 78%
“…A search of the Cambridge Structural Database (Version 5.37; last update February 2016; Groom et al, 2016) for related compounds showed the appearance of the zinc analogue of formula (C 6 H 16 N 2 O)[ZnCl 4 ] (El Glaoui et al, 2008;Lamshö ft et al, 2011), in which the Zn II atom is coordinated by four Cl atoms in a slightly distorted tetrahedral environment ( 4 = 0.93). In spite of a common symmetry and of a certain similitude in the unit-cell parameters, this and the title compound are not isotypic.…”
Section: Database Surveymentioning
confidence: 99%
“…Not only hydrogen-bonding and Coulombic interactions play a significant role (Taylor, 2016;Gavezzotti & Lo Presti, 2016;Lo Presti, 2018), but weak hydrogen bonding has also attracted widespread attention in crystal packing or relative physicochemical properties (Nogueira et al, 2015;Belkova et al, 2016). Nevertheless, there is a debate on the importance of the interaction between a C-HÁ Á ÁX-type (X = O, N and halogen) hydrogen bonds on the crystal packing (Amamou et al, 2017;El Glaoui et al, 2018;Ustabaş et al, 2018). Hence, particular attention is paid to their roles when analyzing a crystal structure.…”
Section: Introductionmentioning
confidence: 99%